Bronastodobno naselje Oloris pri Dolnjem Lakošu = Bronzezeitliche Siedlung Oloris bei Dolnji Lakoš - Dular, Janez (Opera Instituti Archaeologici Sloveniae, 2002)
Archaeological sites whose importance extends beyond a Slovenian framework undoubtedly include the Bronze Age settlement of Oloris near Doljni Lakoš. The site was excavated in the eighties by staff of the Regional Museum in Murska Sobota and members of the Institute of Archaeology, ZRC SAZU, from Ljubljana.